Pengawetan Kayu Karet (Hevea braziliensis MUELL Arg) Menggunakan Asam Borat (H3BO3) Dengan Metode Pengawetan Rendaman Panas Dingin Preserving of Rubber Wood (Hevea braziliensis MUELL Arg) Using Boric Acid (H3BO3) With Cold and Hot Soaking Preservation - Nadya Putri; Evalina Herawati; Ridwanti Batubara (Peronema Forestry Science Journal, 2013)
The objectives of this research were to calculate the amount of retention and penetration scores and to examine the stability of dimension and strength of rubber wood after conserving with boric acid preservative (H3BO3). The method applied in this research was hot and cold soaking . After a test sample was preserved with boric acid, then its retention, penetration, and ASE scores were calculated, and the examination of MOE and MOR was conducted eventually. In this research, the best concentrate was gained at treated concentrate 3 % for the retention score, penetration and ASE scores are 1.39 kg/m2, 0.89 mm, and 2.65 %. While the highest MOE and MOR score was gained at 0% concentrate (controlled) with 17619 kg/m2 and 210 kg/m2. The retention and penetration scores increased as the concentrate increased. But the distribution the preservative was able to decrease the strength of wood. Keywords : preservation, rubber wood, boric Acid, MOE, MOR